The Influence of Cooperative Expenses on Profitability at KPRI colleges in Makassar City - M. Yusuf A. Ngampo; Sahade Sahade (Jurnal Office, 2021)
This study aims to determine the effect of cooperative burden on profitability at the Cooperative Employees of the Republic of Indonesia (KPRI) of Higher Education in Makassar City. The population of this research is all KPRI Universities in Makassar City, while the sample in this study is KPRI Universities in Makassar City which have financial reports for the last five years (2015-2019). Data collection was carried out using documentation techniques. Data analysis was performed using simple regression analysis techniques, correlation coefficient, and t-test. The results showed that an increase in the cooperative burden on the KPRI of Higher Education in Makassar City would result in a decrease in profitability at the KPRI. Vice versa, if the burden of cooperatives has decreased, the profitability of the KPRI of Higher Education in Makassar City will increase. This can occur because the operating expense is one of the deductions from the income in the KPRI to generate SHU. So that if the cooperative load is in a small amount, the resulting SHU is quite large.